Burgeoning single atoms as new types of nanozymes and electrocatalysts for sensing, biomedicine and energy conversion. (23rd August 2021) - Xu, Yun; Yin, Hongyao; Xiao, Fei
Abstract: Single atom catalysts (SACs), featured by atomically-level distributed active sites on supports, provide an ideal platform in the fields of energy conversion, and mimic metalloprotease for bridging the gap between natural enzymes and single atom nanozymes by virtue of their maximum atom utilization efficiency, superior selectivity and outstanding catalytic performance. In this review, the recent progress in this field is reported from the perspectives of synthesis routes, which is also a prerequisite for catalytic investigation. Subsequently, we depict their applications in different sensing systems including electrochemical, colorimetric and photoactive sensing, as well as biomedicine such as disease therapy, antibacterial and cytoprotection to demonstrate their nanoenzymatic activity, and their promising applications in electrocatalysis such as water splitting, oxygen and CO2 reduction reaction are highlighted in more details. Finally, the current challenges and future outlooks of higher loading, more activity and stable in SACs are presented.